Multiple Role Conflicts In The Employment Field In Indonesian Government Agency Institutions with Work Life Balance (WLB) and Job Stress As Mediator Variables on Employee Performance - Farah Fadila; Cutia Wati; Frisca Natasya; Siti Maryam (Journal Research of Social Science, Economics, and Management, 2024)
Work-life balance issues are an important aspect of the psychology of happiness, which is determined by a strong sense of self-worth, satisfaction, and a variety of life-affirming relationships. This study aims to explore how dual role conflicts affect employee performance in the Manpower Office (Disnaker) in Indonesia, by considering the role of work-life balance (WLB) and work stress as mediator variables. The research method used involved collecting data from 154 employees in the disnaker through questionnaires and interviews. The data was then analyzed using statistical analysis techniques to identify the relationship between multiple role conflicts, WLB, work stress, and employee performance. The results showed that dual role conflict had a significant effect on WLB and work stress, but did not affect employee performance levels. Meanwhile, work stress and WLB cannot mediate the dual role with performance. This research provides important insights for human resource management in government agencies to develop policies and programs that support the balance between work and personal life of employees. An emphasis on managing multiple role conflicts and work stress in the work environment can improve employee well-being as well as the overall effectiveness of the organization. The practical implications of this study are the importance of appropriate interventions to improve the working conditions of employees in the public sector, while improving quality public services.